Industrial Estate Spillover and Food MSME Upgrading in Batang - Hima Barima (Journal of Research on Business and Tourism, 2026)
Industrial estate development can create new economic opportunities for local micro, small, and medium-sized enterprises (MSMEs), but these opportunities do not automatically lead to business upgrading. This study examines the effect of industrial estate spillover on food and beverage MSME upgrading in Batang Regency, Central Java, Indonesia, through the mediating roles of absorptive capacity and digital capability, as well as the moderating role of institutional support. A quantitative explanatory approach was applied using data from 350 food and beverage MSME owners, managers, and business operators. The data were analyzed using partial least squares structural equation modeling (PLS-SEM). The findings show that industrial estate spillover positively influences absorptive capacity and MSME upgrading. Absorptive capacity positively affects digital capability and MSME upgrading, while digital capability also contributes positively to MSME upgrading. The mediation results confirm that absorptive capacity and digital capability serve as important mechanisms linking industrial estate spillover to MSME upgrading. Institutional support strengthens the relationship between industrial estate spillover and absorptive capacity. This study concludes that MSME upgrading depends not only on external industrial opportunities but also on learning capability, digital readiness, and institutional support.